Evolution and Esthesiology: Seeing the Eye through Merleau-Ponty’s Nature and Logos Lectures - Hayden Kee (Humana.Mente: Journal of Philosophical Studies, 2023)
In his late lecture course titled “Nature and Logos: The Human Body” (1959-1960), Merleau-Ponty proposed that we understand human symbolism, language, and reason by viewing the human being initially as a variant on animal embodiment and perception prior to being a rational animal. To elaborate this project, he outlined an “esthesiology” informed by the study of evolution. However, in the sketches that survive of “Nature and Logos,” we find neither a detailed explanation of how Merleau-Ponty understood this approach nor its concrete execution with respect to the human body. In this paper I reconstruct Merleau-Ponty’s esthesiology. An animate body possesses two “sides”: it is a sensing organism open onto the world and a sensible part of the natural world. Visual animals such as humans can see, see themselves, and be seen by others. To understand their way of life, we must study not only the body’s capacities for perception and action, but also how those capacities are seen by other organisms, especially conspecifics. The body’s visibility shapes the social prospects of a species and its potential for developing complex sociality, language, and cognition. I apply this basic esthesiological principle to study the human eye. Both in its vision and its visibility, the human eye is a distinctive variation of animality and one that conditions and shapes human sociality and cognition. I develop this insight with respect to a central philosophical theme of Merleau-Ponty’s late work, the relation of the visible and the invisible. I conclude by discussing the importance of Merleau-Ponty’s esthesiology for his late thought and current discussions of the naturalization of phenomenology.